Gold–silver alloy semi-nanoshell arrays for label-free plasmonic biosensors. Issue 28 (11th July 2017) - Russo, Valentina; Michieli, Niccolo'; Cesca, Tiziana; Scian, Carlo; Silvestri, Davide; Morpurgo, Margherita; Mattei, Giovanni
Abstract : The label-free bio-sensing properties of bimetallic Au–Ag semi-nanoshell ordered arrays can be enhanced by tuning their lateral coupling. Abstract : Nanosphere lithography coupled with reactive ion etching has been used to synthesize hexagonal ordered arrays of Au–Ag bimetallic semi-nanoshells to be used as plasmonic biosensors. The degree of lateral interaction between adjacent semi-nanoshells can be controlled by tailoring the reactive ion etching time in order to boost the global plasmonic properties through the formation of near-field hot-spots, which in turn can improve the sensitivity of the biosensors. To test the efficiency of the proposed system as a biosensor, we used an established protocol for the detection of biomolecules (local sensitivity), based on the receptor–ligand approach and using the biotin–streptavidin model system. We also tested the sensitivity to a homogeneous change in the refractive index of the buffer over the sensor (bulk sensitivity). Comparing the obtained results to those of an array of nanoprisms, chosen as a benchmark, significantly higher performances both in local and bulk sensitivities have been found, in agreement with electrodynamics simulations based on finite-element methods.